Strategies for Environmental, Economic, and Social Sustainability of Potato Agriculture in Dieng plateau Central Java Indonesia - WIDAYATI, Tri; WARIDIN, WARIDIN; YUSUF, Edy (Journal of Environmental Management and Tourism; Vol 8 No 1 (2017): JEMT Volume VIII Issue 1(17) Spring 2017, 2017)
Environmental problems in Dieng Plateau area, Central Java, Indonesia have no longer conformed to the principles of ecology, in which the use of fertilizers and pesticides is very high and productivity has decreased. Potato farming system causes the land condition becomes critical which could negatively affect the system of sustainable agricultural development. This study aims to analyze sustainable agriculture management in Dieng Plateu using indicators of economic, environmental and social. This study employed a combination of quantitative and qualitative method. Quantitative method was used to answer questions regarding economic, social, and environmental aspects. The economic aspect of sustainable agriculture included income, productivity and calculation of return cost ratio, and technical efficiency. Calculations on the use of organic fertilizer and manure, erosion hazard level and quality of water were included in the environmental aspect. The social aspect included education level, and housing conditions. Qualitative method was used to analyze the institutional model related to the conditions of Dieng area. The findings showed that potato farming indicators index was 48.57 and classified as unsustainable.